Literacy media models in improving reading skill of early class students in elementary school - Elfia Sukma; Ritawati Mahjuddin; M. Habibi (Journal of Counseling and Educational Technology, 2018)
This research is based on  low quality of literacy mediais used by teachers in teaching reading in the early grades in elementary school. Therefore, this study aimed to produce a valid literacy media, practical, and effective in improving reading skills of elementary school students beginning classes. The subject of research is early elementary grade students in the District of North Padang, Padang City. Literacy media is being developed is a big book, image media, and calendar stories. Development activity using 4-D model of the stages define, design, development, and disseminate. Data obtained from the results of a validation study of literacy media, observation, use of literacy media, and the learning outcomes of students' reading skills after using the media developed. The results showed that literacy mediais developed make students interested in reading and feel happy with reading material, thus helping to increase students' understanding of the content of reading.Based on these results, can conclude that the model developed literacy mediahas been a valid, practical and effective use to improve reading skills early elementary grade students.